2022
DOI: 10.3389/fphar.2022.851508
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Alkaloids Derived From Traditional Chinese Medicine in Pain Management

Abstract: Chronic pain is one of the most prevalent health problems. The establishment of chronic pain is complex. Current medication for chronic pain mainly dependent on anticonvulsants, tricyclic antidepressants and opioidergic drugs. However, they have limited therapeutic efficacy, and some even with severe side effects. We turned our interest into alkaloids separated from traditional Chinese medicine (TCM), that usually act on multiple drug targets. In this article, we introduced the best-studied analgesic alkaloids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 209 publications
(312 reference statements)
0
12
0
Order By: Relevance
“…Sinomenine (SIN) is extracted from CAULIS SINOMENII, which is the main active ingredient of Zhengqing Fengtongning capsule ( 90 ). Many studies demonstrated sinomenine could alleviate morning stiffness and joint pain in the RA patients, by modifying neurotransmission, inhibiting cyclooxygenase 2-dependent prostaglandin E2 and NO, TNF, INF-γ, IL-6, IL-1β, and IL-4, and suppressing the activity of P38 MAPK, MMPs, and NF-κB ( 91 , 92 ). At the same time, SIN could regulate immunity and alleviate inflammation by inhibiting T- lymphocyte and B-lymphocyte activation ( 93 ), regulating NLRP3 inflammasome and NF-κB pathway ( 94 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sinomenine (SIN) is extracted from CAULIS SINOMENII, which is the main active ingredient of Zhengqing Fengtongning capsule ( 90 ). Many studies demonstrated sinomenine could alleviate morning stiffness and joint pain in the RA patients, by modifying neurotransmission, inhibiting cyclooxygenase 2-dependent prostaglandin E2 and NO, TNF, INF-γ, IL-6, IL-1β, and IL-4, and suppressing the activity of P38 MAPK, MMPs, and NF-κB ( 91 , 92 ). At the same time, SIN could regulate immunity and alleviate inflammation by inhibiting T- lymphocyte and B-lymphocyte activation ( 93 ), regulating NLRP3 inflammasome and NF-κB pathway ( 94 ).…”
Section: Discussionmentioning
confidence: 99%
“…There has been considerable research into the analgesic effects of compounds, notably alkaloids, contained in CHMs. 64 The included studies often tested multi-ingredient formulations, each of which contained multiple compounds, so it was not possible to determine which, if any, contributed to the clinical effect. In addition, the studies of multi-ingredient topical formulations generally did not provide the rationale for including each ingredient, so we cannot be certain that they were intended to exert anti-nociceptive effects.…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition, TTMP is also an important active component of Chuanxiong rhizome (Szechuan Lovage Rhizome), and it can be applied to the treatment of cardiovascular and cerebrovascular diseases. 6 Further, it has favorable curative effects on ischemic cardiovascular and cerebrovascular diseases in clinical practice. 7 According to some studies, TTMP in Baijiu can dilate blood vessels, improve microcirculation, and inhibit platelet aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…It is a nitrogen‐containing heterocyclic compound characterized by a roasting and sweet aroma, and one of the important aroma compounds in Baijiu 5 . In addition, TTMP is also an important active component of Chuanxiong rhizome ( Szechuan Lovage Rhizome ), and it can be applied to the treatment of cardiovascular and cerebrovascular diseases 6 . Further, it has favorable curative effects on ischemic cardiovascular and cerebrovascular diseases in clinical practice 7 .…”
Section: Introductionmentioning
confidence: 99%